The effectiveness of the use of anaerobic exercises to develop your stamina with players young people between the ages of fencing 15-17years - Ghalib, Ishraq (Journal of Physical Education, 2013)
Each stage of the sports training goals must be achieved to continue in the direction of the ultimate goals of the training is the most important characteristic of stage training players young people in the sport of fencing is the interest of preparing your physical, especially as the players have achieved a high level in motor skills and basic skills in the earlier stages and through Note the researcher being the coach of the game and inform them of the number of training units noticed a weakness in carrying power and carry speed characterized the performance of the players and the lack of training curricula to effective special units designed to develop your endurance so felt researcher to do this study. The study aims to - Preparation for the development of training curriculum bearing strength and speed using anaerobic exercise -see the effect in the development of anaerobic exercises carry the speed and power of young players in the duel It consists research community of (15) player representing the players club girl athlete of the season 2012-2013 Testing was performed tribal members of the study followed by the application of a training curriculum included exercises anaerobic after tests were conducted dimensionality where followed researcher experimental method and after processing the data statistically reached researcher to a number of conclusions the most important. -anaerobic exercises a positive impact in the evolution of carrying power and carry speed in young players in fencing The researcher has raised several recommendations including Interest in developing special physical qualities is the most important bearing strength and carry speed. -the use of anaerobic exercise by the trainers to develop a recipe bearing strength and carry speed in young players in the sport of fencing